(untitled) - McQueen, Mike (Washington, 2003)
The book concludes with an examination of the emerging concept of green infrastructure -- a strategic approach to conservation that involves planning and managing a network of parks, natural areas, greenways, and working lands that can help support native species, maintain ecological processes, and contribute to the health and quality of life for America’s people and its communities. Land Conservation Financing is an indispensable resource for land conservationists in the public and private sectors who are looking for a detailed, national portrait of the state of land conservation in America today.
Keywords: Land use,Land use,Land trusts,Open spaces,Conservation of natural resources,Bảo tồn nguồn tài nguyên thiên nhiên,Sử dụng đất; Planning,Government policy,Finance,Finance,Tài chính,Chính sách nhà nước; United States,United States,United States,United States,United States,Hoa Kỳ,Hoa Kỳ